Analysis of the consumptive behavior of Muslim consumers: A study on social, psychological, and financial literacy - Munir, Munir; Mais, Rimi Gusliana; Achmad, Aisah; Nuryati, Tutty; Sakti, Sri Handoko (LPMP Imperium, 2023)
This research aimed to examine how social, psychological, and financial literacy factors influence the online shopping behavior of college students. The study included 350 undergraduates from Jakarta who were selected using a convenience sampling method. The data was analyzed using regression analysis, which revealed that social and psychological factors significantly negatively impact students' online shopping behavior. On the other hand, financial literacy has a significantly positive impact. This study gives students and the community important insights into managing finances effectively and avoiding impulsive purchases of unnecessary items. Public interest statement As the Muslim population continues to grow, it becomes increasingly important to understand the values, preferences, and needs of Muslim consumers. This knowledge can help businesses develop relevant products, improve marketing strategies, and build stronger relationships with their target markets. This study provides valuable insights into consumer behavior, particularly among Muslim consumers.